2013
DOI: 10.3390/ijerph10010347
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Full-Facepiece Respirator Fit on Fire Fighters in the Municipality of Jeddah, Saudi Arabia

Abstract: The purpose of this study was to assess the effect of personal variables on the fit of the respirators used by firefighters and workers in highly polluted environments. However, resistance from many plants managers was met to conduct the study on their workers. Therefore, we were forced to limit the study on firefighters who were found very cooperative. Forty volunteer firefighters from different departments participated in the study. They were subjected to a daily leak rate measurement using a Control Negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Zhuang et al pointed to the fact that the face length and face width would be as key facial dimensions for selecting the best respirator fitted into wearers' face, besides, face size categories matched respirator sizing remarkably well [36]. Balkhyour et al discussed that face shape played an important role in providing the optimal respirator fitted into the firefighters' facial dimensions [45]. Oestenstad et al reinforced that fit assessment of the different brands of respirators on the same subject resulted in significant differences in respirator fit [17].…”
Section: Introductionmentioning
confidence: 99%
“…Zhuang et al pointed to the fact that the face length and face width would be as key facial dimensions for selecting the best respirator fitted into wearers' face, besides, face size categories matched respirator sizing remarkably well [36]. Balkhyour et al discussed that face shape played an important role in providing the optimal respirator fitted into the firefighters' facial dimensions [45]. Oestenstad et al reinforced that fit assessment of the different brands of respirators on the same subject resulted in significant differences in respirator fit [17].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have already shown that the causes of lack of fitness between respirators and the wearer's face are the face shape and the presence or absence of a beard. 24 , 25 , 26 In this study, we did not collect face shape data; however, we checked whether they had beards and used towels around the mouth and facial knits cover during the mask fit test. The reason for investigating the use of towels and facial knits covers is that, as with beards, they are the reason for creating a gap between the respirator and face, and they are related to increased air leaks.…”
Section: Discussionmentioning
confidence: 99%
“…56 A beard usually precludes a good fit and proper seal. [60][61][62] As the fit is one of the most important factors for effectiveness, more research needs to be done on improving the fit of respirators and masks.…”
Section: Open Accessmentioning
confidence: 99%